Special endurance of highly qualified judoists and the method of its quantitative assessment in preparation for responsible competitions - Shiyan, V.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to substantiate methods for assessing the level of development of special endurance of wrestlers on the basis of a comprehensive definition of pedagogical and biochemical indicators characterizing the effectiveness of performing a standard specific task with throws of a wrestling dummy. Methods and structure of the study. As a result of exploratory research, the author developed a standardized test program with deflection throws of a wrestling dummy and a criterion for quantifying the level of special endurance of judo wrestlers. Based on the results of long-term observations of the dynamics of special endurance of highly qualified judoists, guidelines for a quantitative assessment of the special endurance of athletes at various stages of training are proposed. The author notes that the program of precompetitive training of wrestlers should be focused on achieving a level of special endurance that exceeds the limit value of the coefficient of special endurance (CSE) of more than five conventional units. With this level of special endurance, the load of a competitive duel does not lead to a pronounced activation of anaerobic glycolysis. The pH values ​​after the fight will be in the optimal values ​​(7.2-7.27 c.u.).